2012
DOI: 10.1016/j.lpm.2011.11.026
|View full text |Cite
|
Sign up to set email alerts
|

La production scientifique issue de la formation initiale à la faculté de médecine d’Angers entre 2002 et 2008 : de bonne qualité mais insuffisante

Abstract: Scientific publications issued from initial medical education at the Faculty of Medicine of Angers was of good quality but quantitatively insufficient, and contributed poorly to the University Hospital funding despite a significant number of diplomates. Logistical support should be considered in order to promote scientific production after initial medical education.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
0
1
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 13 publications
1
0
1
1
Order By: Relevance
“…The percentage of derivative articles published by students during the doctoral studies and postdoctoral period in our study was 20.1%. This data is comparable to a survey by Pitche et al (2007) among faculties, where "theses represented only 21.6% of these publications" [articles in indexed journals] and Baufreton et al (2012) that conducted searches in databases with surveys of validation among theses supervisors and found that 165 theses from the School of Medicine of Angers, France, produced 28% of publications, out of 97 (16%) indexed in PubMed.…”
Section: Discussionsupporting
confidence: 75%
“…The percentage of derivative articles published by students during the doctoral studies and postdoctoral period in our study was 20.1%. This data is comparable to a survey by Pitche et al (2007) among faculties, where "theses represented only 21.6% of these publications" [articles in indexed journals] and Baufreton et al (2012) that conducted searches in databases with surveys of validation among theses supervisors and found that 165 theses from the School of Medicine of Angers, France, produced 28% of publications, out of 97 (16%) indexed in PubMed.…”
Section: Discussionsupporting
confidence: 75%
“…Specifically, lack of writing experience was found in a previous study, suggesting that PhD students with a medical background did not receive sufficient training in writing as part of their curriculum [20,21], although possible solutions were not evaluated. In contrast to this study, other studies among hospital trainees, surgeons and researchers have identified further barriers to writing: mainly limited time, but also limited data, remote working, lack of logistical resources, cognitive burden, and perceiving plagiarism as a threat [8][9][10]20,22]. This difference might be explained by a difference in the participants' circumstances, as the PhD students in this study had a structured program with a clear and approved timeline as part of their study plan.…”
Section: Barrierscontrasting
confidence: 58%
“…En plus des informations sur le nombre d'articles (et leur répartition A, B, C, D, E), les données SIGAPS ont permis de repérer des établissements surspécialisés sur la MA, d'analyser les domaines sur lesquels portaient les publications, mais aussi d'identifier les recherches associées et les collaborations.Ce travail repose sur SIGAPS, conçu pour analyser l'activité de recherche du CHU de Lille, et utilisé depuis pour la répartition nationale des crédits MERRI. Il illustre l'utilisation plus stratégique que financière qui peut être faite de SIGAPS, ce qui renforce la nécessité d'en connaître les limites méthodologiques.Bien que SIGAPS soit jugé robuste[20], peu de travaux d'évaluation scientifique ont été réalisés à partir de ses données[21][22][23][24][25]. L'interrogation nominative de PubMed, et non sur les adresses peu fiables (2700 variantes identifiées pour le CHU de Lille entre 1990 et 2014), et la validation des publications par les chercheurs eux-mêmes, sont les deux piliers méthodologiques qui assurent la fiabilité des données SIGAPS d'un chercheur, d'un établissement ou d'une inter région.…”
unclassified